Spinosaurid Dinosaurs from the Early Cretaceous of North Africa and Europe: Fossil Record, Biogeography and Extinction - Candeiro, Carlos Roberto A.; Brusatte, Stephen L.; Souza, André Luis de (Anuário do Instituto de Geociências, 2019)
We review the fossil records of spinosaurid dinosaurs in order to discuss this group’s evolution and distribution in Europe and North Africa during the Early Cretaceous. Along with their eastern Laurasian distribution during the Cretaceous, these theropods have been found in coastal deposits of Europe and North Africa dated from the Barremian to the Cenomanian. The main occurrences of spinosaurid remains are in the deposits of northern Gondwana and western Laurasia, which suggests that these regions were very important in spinosaurid evolution prior to the Cenomanian. Later, spinosaurids were seemingly replaced in northern Gondwana by other top predator groups, including the abelisauroids.